Influencing Factors and Intervention Strategies of Early Mathematical Cognition - Cui, Xiaoying (Pinnacle Academic Press Proceedings Series, 2026)
Early mathematical cognition constitutes a critical foundation for children’s subsequent academic achievement and broader cognitive development. Its growth is shaped by multiple interacting factors, including the family environment, parental beliefs and behaviors, school experiences, and the increasing presence of digital resources in children’s daily lives. With the rapid popularization of information technology and the transformation of family education models, clarifying the mechanisms through which these factors operate has important theoretical and practical significance. This review synthesizes major theoretical perspectives on early mathematical cognition, such as number sense, spatial reasoning, and logical thinking, and summarizes empirical findings on how family learning atmosphere, parent–child interaction, and guided use of digital tools support these core abilities. Particular attention is given to the complementary roles of family-based activities and digital learning platforms, which together can enrich children’s opportunities for mathematical exploration and practice. The review further discusses intervention strategies at the levels of parents, schools, and communities, including parental education programs, guidance on the selection and use of digital resources, curriculum optimization, and multi-agency collaboration. Current research is limited by a predominance of cross-sectional designs, insufficient longitudinal and causal evidence, and a lack of attention to cultural and socioeconomic diversity. Future studies should adopt diversified, long-term, and cross-cultural approaches to refine evidence-based interventions and promote the sustainable development and wider dissemination of high-quality early mathematics education.